PENGARUH MEDIA POP UP BOOK TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA SEKOLAH DASAR - Putri, Tazira Dwi; Rambe, Riris Nurkholidah (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
The aim of this research was to determine how Pop-Up Book media influences the learning outcomes of class V students at MIN 1 Deli Serdang on Jl. Pasar XV Medan Sinembah District. Tanjung Morawa District. Deli Serdang. This research is quantitative research using the Quasi Experiment method. This study used a nonequivalent control group design. The population that will be the research sample is class V A and class V B MIN 1 Deli Serdang. Research data analysis used a t-test which was processed with the help of SPSS 25 software with a sig (2-tailed) value of 0.002 0.05 in the experimental class. It can be concluded that there is an influence of pop-up book media on student learning outcomes in class V Indonesian language learning at MIN 1 Deli Serdang, because Pop-Up Book media can have a positive impact on students both in understanding the material, sharpening their thinking skills and inviting students to be more active and skilled in solving problems related to Indonesian language learning material.